The Needs for Musical Instruments from Recycled Materials of the Elderly: A Case Study of Tha Pho Subdistrict, Mueang District, Phitsanulok Province - Boonrod, Vich (Journal of Community Development Research (Humanities and Social Sciences); Vol 17 No 3 (2024): July - September 2024, 2024)
This paper presents a qualitative case study investigating the needs for musical instruments from recycled materials of elderly people living in Tha Pho Subdistrict, Mueang District, Phitsanulok Province, Thailand. In-depth semi-structured interviews were conducted with a purposefully selected group of five elderly volunteers aged 60-75 residing in Tha Pho Subdistrict who met the following inclusion criteria: ability to participate in musical activities independently, ability to read and write, and living in Tha Pho Subdistrict.           The findings revealed a variety of musical instrument preferences and emphasized the importance of culturally sensitive interventions to promote musical engagement among the elderly. Regarding design considerations, user-centered approaches should be prioritized, focusing on usability, tactility, and lightweight construction. Instruments were crafted from materials that were visually accommodating, aesthetically pleasing, and devoid of sharp edges. Physical aspects were tailored to the anatomy of older individuals, with floor-standing designs to mitigate lifting strains for comfort and health promotion. As for the selection of materials, it prioritized safety, availability, and minimizing injury risks during playing. Additionally, instruments should be designed for easy access and playability, utilizing natural materials where possible. The choice of music for playing was curated to resonate with the elderly, featuring familiar tunes or reflecting their cultural heritage, such as “Pleng Lao Long Nan” and “Pleng Pan Fai”. Keywords: Music, Elderly, Musical Instrument, Recycled Materials